Characterizing bed roughness on the Antarctic continental margin - Santiago Munevar Garcia; Lauren Elizabeth Miller; Francesca Anna Maria Falcini; Leigh Asher Stearns (Journal of Glaciology)
Spatial variability in bed topography, characterized as bed roughness, impacts ice-sheet flow and organization and can be used to infer subglacial conditions and processes, yet is difficult to quantify due to sparse observations. Paleo-subglacial beds of formerly expanded glaciers found across the Antarctic continental shelf are well preserved, have relatively limited post-glacial sediment cover and contain glacial landforms that can be resolved at sub-meter vertical scales. We analyze high-resolution bathymetry offshore of Pine Island and Thwaites glaciers in the Amundsen Sea to explore spatial variability of bed roughness where streamlined subglacial landforms allow for the determination of ice-flow direction. We quantify bed roughness using std dev. and Fast Fourier Transform methods, each employed at local (100 km) and regional (101–2 km) scales and in along- and across-flow orientations to determine roughness expressions across spatial scales. We find that the magnitude of roughness is impacted by the parameters selected – which are often not sufficiently reported in studies – to quantify roughness. Important spatial patterns can be discerned from high-resolution bathymetry, highlighting both its usefulness in identifying patterns of streaming ice flow and underscores the need for a standardized way of characterizing topographic variability.